2020
DOI: 10.1371/journal.pone.0236453
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma microRNAs biomarkers in mild cognitive impairment among patients with type 2 diabetes mellitus

Abstract: Objectives To assess the potential value of some miRNAs as diagnostic biomarkers for mild cognitive impairment (MCI) among patients with type2 diabetes mellitus (T2DM) and to identify other risk factors for MCI among them. Methods This study enrolled 163 adults with T2DM using face to face interview. Cognitive function with its domains was assessed using Adenbrooke’s Cognitive Examination III (ACE III). Lipid profile, glycated hemoglobin, and miR-128, miR-132, miR- 874,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Serum levels of miR-132 were upregulated in MCI patients, correlated significantly with the cognitive assessment score [ 209 ], and correctly separated MCI patients from age-matched healthy controls [ 210 ]. A recent study involving 163 participants reported that the plasma levels of miR-132 were significantly higher in T2DM patients with MCI compared to normally cognitive subjects [ 20 ].…”
Section: Biomarkers Of Cognitive Dysfunctions In Type 2 Diabetes Mell...mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of miR-132 were upregulated in MCI patients, correlated significantly with the cognitive assessment score [ 209 ], and correctly separated MCI patients from age-matched healthy controls [ 210 ]. A recent study involving 163 participants reported that the plasma levels of miR-132 were significantly higher in T2DM patients with MCI compared to normally cognitive subjects [ 20 ].…”
Section: Biomarkers Of Cognitive Dysfunctions In Type 2 Diabetes Mell...mentioning
confidence: 99%
“…Besides the early changes in cerebral metabolism and brain structures that can be detected using brain imaging technology platforms [ 4 ], the most promising molecules identified so far are related to glucose metabolism, inflammation, neurodegeneration, vascular damage, and oxidative stress. Some of these molecules include C reactive protein (CRP) [ 12 ], interleukin-6 (IL-6) [ 13 ], leptin and interleukin-1 (IL-1 β) [ 14 ], homeostasis model assessment of the insulin resistance (HOMA-IR) score along with glycosylated hemoglobin (HbA1c) [ 15 ], advanced glycation end products (AGEs) [ 16 ], tau protein [ 17 ], glycogen synthase kinase 3β (GSK-3β) [ 18 ], brain-derived neurotrophic factor (BDNF) [ 19 ] and microRNAs [ 20 ]. In the following sections, we aim to evaluate the contributory risk factors and the potential pathophysiological mechanisms of cognitive disorders in diabetes, and to discuss the potential biomarkers related to the cognitive decline in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cognitive domains related to posterior brain regions, primarily involved in visuospatial, visual perceptual abilities, and constructive practice regions are mainly altered in patients with MHE[ 172 ]. Moreover, T2DM as an EHM in HCV infected patients may be associated with cognitive impairments[ 177 ]. Conversely, some studies did not confirm the association between chronic HCV infection and neurologic disorders[ 178 ].…”
Section: Extrahepatic Manifestations Of Chronic Hepatitis C Virus Inf...mentioning
confidence: 99%
“…With the accelerated pace of global population aging, type 2 diabetes mellitus (T2DM), one of the most common diseases among the elderly, has attracted more and more attention. Many studies have demonstrated that the negative effects of T2DM on cognitive function have significant clinical significance [ 1 , 2 ]. In the course of diabetes, patients are more likely to progress to cognitive impairment and dementia, both can seriously affect the patients’ self-management, further exacerbating the disease and leading to more complications [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the negative effects of T2DM on cognitive function have significant clinical significance [ 1 , 2 ]. In the course of diabetes, patients are more likely to progress to cognitive impairment and dementia, both can seriously affect the patients’ self-management, further exacerbating the disease and leading to more complications [ 1 , 3 ]. Therefore, studies on risk factors for cognitive decline in T2DM patients have been carried out extensively.…”
Section: Introductionmentioning
confidence: 99%